Clinical Pharmacy Services in Heart Failure: An Opinion Paper from the Heart Failure Society of America and American College of Clinical Pharmacy Cardiology Practice and Research Network. Issue 5 (3rd May 2013) - Milfred‐LaForest, Sherry K.; Chow, Sheryl L.; DiDomenico, Robert J.; Dracup, Kathleen; Ensor, Christopher R.; Gattis‐Stough, Wendy; Heywood, J. Thomas; Lindenfeld, JoAnn; Page, Robert L.; Patterson, J. Herbert; Vardeny, Orly; Massie, Barry M.
<x xml:space="preserve">Abstract</x> Heart failure (HF) care takes place in multiple settings, with a variety of providers, and generally involves patients who have multiple comorbidities. This situation is a "perfect storm" of factors that predispose patients to medication errors. The goals of this paper are to outline potential roles for clinical pharmacists in a multidisciplinary HF team, to document outcomes associated with interventions by clinical pharmacists, to recommend minimum training for clinical pharmacists engaged in HF care, and to suggest financial strategies to support clinical pharmacy services within a multidisciplinary team. As patients transition from inpatient to outpatient settings and between multiple caregivers, pharmacists can positively affect medication reconciliation and education, assure consistency in management that results in improvements in patient satisfaction and medication adherence, and reduce medication errors. For mechanical circulatory support and heart transplant teams, the Centers for Medicare and Medicaid Services considers the participation of a transplant pharmacology expert (e.g., clinical pharmacist) to be a requirement for accreditation, given the highly specialized and complex drug regimens used. Although reports of outcomes from pharmacist interventions have been mixed owing to differences in study design, benefits such as increased use of evidence‐based therapies, decreases in HF hospitalizations and emergency department visits, and decreases in all‐cause readmissions have been demonstrated. Clinical pharmacists participating in HF or heart transplant teams should have completed specialized postdoctoral training in the form of residencies and/or fellowships in cardiovascular and/or transplant pharmacotherapy, and board certification is recommended. Financial mechanisms to support pharmacist participation in the HF teams are variable. Positive outcomes associated with clinical pharmacist activities support the value of making this resource available to HF teams.